Sustainability Risk Management (SRM): An Extension of Enterprise Risk Management (ERM) Concept (International Journal of Management and Sustainability, 2016)
This paper aims to provide an insight of the Malaysian experience in terms of Risk Management practices and the integration of the sustainability as part of the enterprise risk management (ERM). Sustainability has been a paradigm shift in the business operations nowadays. The awareness by most of the companies in the world towards the environmental perils leads to the sustainability development. By emphasizing the sustainability risk management (SRM) and the sustainability agendas as part of corporate strategy, it’s not only effecting on the company’s financial performance but also maintaining the longer term of survival in the industry.